Developing a Valid and Reliable Environmental Attitude Instrument for High School Student - Yusup, Febrianawati; Munandar, Achmad (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
This study aimed to develop a valid and reliable instrument to be used for measuring high school students’ attitude toward environment. A six-step model was used in the development of instrument adoption of Ugulu et al (2013). These stages are development of item pool, validation of item pool, taking expert opinions, pilot testing, administration of the instrument, and calculating validity and reliability of instrument. This instrument contains of eight dimensions, covers on attitude toward people, attitude toward flora and fauna, attitude toward earth, attitude toward water, attitude toward air, attitude toward land, and attitude toward waste. Validation stage was submitted to one environmental expert, one pedagogic expert, two high school biology teachers, and two faculty members. The pilot testing of instrument has been carried out with a group of 30 students. Widely pilot testing involves 60 students. Results of this study show that twenty five items fit to use for measuring high school students’ environmental attitude. Twenty five item consist of positive item and negative item in eight dimensions on five-point Likert type scale. The alpha Cronbach coefficient is 0,668. According to these findings, it can be concluded that instrument is a valid and reliable that can be used to measure environment attitude of high school students.Keywords:assessment, environmental attitude, senior high school student